Visible-Light-Active Titania Photocatalysts: The Case of N-Doped TiO2s—Properties and Some Fundamental Issues - Alexei V. Emeline; Vyacheslav N. Kuznetsov; Vladimir K. Rybchuk; Nick Serpone (International Journal of Photoenergy)
This article briefly reviews some factors that have impacted heterogeneous photocatalysis with next generation TiO2 photocatalysts, along with some issues of current debate in the fundamental understanding of the science that underpins the field. Preparative methods and some characteristics features of N-doped TiO2 are presented and described briefly. At variance are experimental results and interpretations of X-ray photoelectron spectra (XPS) with regard to assignments of N 1s binding energies in N-doped TiO2 systems. Relative to pristine nominally clean TiO2 with absorption edges at 3.2 eV (anatase) and 3.0 eV (rutile), N-doped TiO2s display red-shifted absorption edges into the visible spectral region. Several workers have surmised that the (intrinsic) band gap of TiO2 is narrowed by coupling dopant energy states with valence band (VB) states, an inference based on DFT computations. With similar DFT computations, others concluded that red-shifted absorption edges originate from the presence of localized intragap dopant states above the upper level of the VB band. Recent analyses of absorption spectral features in the visible region for a large number of doped TiO2 specimens, however, have suggested a common origin owing to the strong similarities of the absorption features, and this regardless of the preparative methods and the nature of the dopants. The next generation of (doped) TiO2 photocatalysts should enhance overall process photoefficiencies (in some cases), since doped TiO2s absorb a greater quantity of solar radiation. The fundamental science that underpins heterogeneous photocatalysis with the next generation of photocatalysts is a rich playing field ripe for further exploration.